Provision of Health Education as An Effort To Prevent and Control Hypertension in The Elderly in Cikondang Hamlet, Datar Village, Cilacap District - F, Rismayatul; NF, Norma; S, Hernani; WB, W Mahardika; A, Mila; FM, Agis; S, Fajar; G, Gungun; Aji W, M Suci; Saripin, Saripin; P, Rizky; Nugraha, Fajar (AbdimasMu UMTAS, 2024)
Elderly is someone aged 60 years and over. The elderly are said to be at risk for various degenerative diseases compared to young people. One of the degenerative diseases that often occurs without symptoms is hypertension. Hypertension is called the “silent killer” because it can appear without any symptoms or warning signs, so many are not aware of it. The causes of delays in handling patients with hypertension are the majority of patients coming to health facilities when complications have occurred, and the lack of public access to health services, resulting in a lack of control over their disease state, especially in the elderly. Therefore, by conducting counseling related to hypertension, it is hoped that the role of cadres in preventing and controlling hypertension in the elderly can run optimally. This counseling aims to increase the understanding of cadres on the prevention and control of hypertension in the elderly. The main target of this program is health cadres in Cikondang Hamlet, Datar Village, Dayeuh Luhur District, Cilacap Regency. This activity includes an initial survey related to hypertension in the elderly, and conducting counseling on prevention and control of hypertension in the elderly using counseling methods and interactive discussions. The result of this community service activity is an increase in the understanding of health cadres related to Hypertension, especially efforts to prevent and control hypertension in the elderly in Cikondang Hamlet, Datar Village, Dayeuh Luhur District, Cilacap Regency.